Antioxidant and anti hyperglycaemic activities of Aquilaria sinensis leaves (Gaharu) / Ranjitah V. Rajah - Ranjitah V. , Rajah (2018)
Aquilaria sinensis is commonly known as Gaharu belongs to the family of Thymelaeceae. It has been used as traditional medicine for diabetes treatment and possesses several other pharmacological activities. The objective of the present study is to determine the antioxidant and anti hyperglycaemic properties in the A. sinensis leaves. The methanolic leaves extract of A. sinensis was fractionated via solvent – solvent extraction using n-hexane, dichloromethane, butanol, chloroform, ethyl acetate and methanol aqueous to produce fractions. The TLC results of the plant extracts showed the presence of phenolic, terpenoid and alkaloid compounds. The total phenolic contents is the highest in the ethyl acetate extract at 1.69 ± 0.02 mg GAE/ g dry weight and the total flavonoid content highest in butanol fraction extract at 3.59 ± 0.07 mg QE / g dry weight. The fractions were subjected to the in vitro antioxidant assay. The results showed that ethyl acetate fraction exhibited the higher scavenging DPPH radicals activity with IC50 value of 0.10 ± 0.02 mg/ml, the highest ability of ferric reducing power activity at 0.37 ± 0.07 mmol/g extract , and good chelating of metal with IC50 < 0.05 ±0.01 mg/ml. However, methanol aqueous exhibits the highest scavenging of superoxide radical activity with IC50 value of 0.18 ± 0.01 mg/ml, nitric oxide radical scavenging activity with IC 50 >1.6 ± 0.001 mg/ml. Based on the results obtained from the antioxidant assays, the fractions which showed good antioxidant activities were subjected to in vitro anti hyperglycaemic assay. Among all of the active fractions, ethyl acetate showed the highest inhibition of alpha amylase enzyme at 43.14% with IC50 value of >1.6 ± 0.04 mg/ml, inhibition of alpha glucosidase enzyme at 81.06% with IC50 value of < 1.6 ± 0.03 mg/ml, inhibition of glycogen phosphorylase at 17 % with IC50 value of >1.6 ± 0.09 mg/ml and inhibition of haemoglobin glycosylation at 65.25 % with IC50 value of 0.87 ± 0.12 after 72 hours of incubation. However, all of the fractions showed poor inhibition on glycogen phosphorylase enzyme activity. The results from the LCMS analysis showed the presence of a bioactive compound, magniferin in aqueous fraction and tripteroside in ethyl acetate fraction. Those compounds are actively known to have the properties of anti hyperglycaemic and antioxidant. In conclusion, the leaves of the A. sinensis possessed antioxidant and anti hyperglycaemic activity that provide scientific evidence to support the claim of traditional medicinal or herbal medicinal in treating diabetes.